A Coding and Classification as an Aspect af System Flexibility in Sheer Metal Manufacturing - Vojo Visekruna; Darko Petkovic (Communications - Scientific letters of the University of Zilina, 2000)
Industry increasingly faces the need to respond rapidly and effectively to ever changing market demand. This need is partially met by introducing a high degree of flexibility into all industry phases, especially manufacturing. Group technology idea has been widely applied to the metal cutting area. In many instances, significant productivity gains have been achieved. However, very little work has been reported in applying GT in the sheet metal manufacturing. Sheet metal parts produced in sheet metal process with/without plastic deformation (pressing, punching, bending, etc) are on the increase. These processes are becoming one of the major manufacturing processes. One possible reason for the limited GT application in sheet metal manufacturing could be the lack of a suitable coding and classification system. Results indicated here say that the proposed GT concept would increase production system flexibility.